PENDAMPINGAN DAN PENINGKATAN KUALITAS ANALISIS DATA DALAM PUBLIKASI ILMIAH BAGI CIVITAS AKADEMIK STIKES MAJAPAHIT MOJOKERTO - Bambang Widjanarko Otok; Jorge Mateu; Purhadi; Sutikno; Santi Wulan Purnami; Jerry Dwi Trijoyo Purnomo; Achmad Choiruddin; Shofi Andari; Eka Diah Kartiningrum (Jurnal Pengabdian Masyarakat, 2024)
Efforts to assist and improve the quality of data analysis in scientific publications for the academic community of Stikes Majapahit Mojokerto are held as an effort to increase the achievement of scientific publications in reputable publications which are very important to improve the accreditation status of universities. The purpose of this activity is to improve participants' understanding of the preparation of reputable scientific articles, participants' ability to model in SEM using AMOS, and the ability of the academic community to write and discuss the results of modeling analysis in scientific articles. This activity was carried out from April-June 2023 at Stikes Majapahit Mojokerto. The results of the activity showed an increase in participants' understanding of the concepts of SEM and Multivariate, CFA and path analysis and scientific article management. This activity should be an annual event that can boost the achievement of scientific publications, especially in the health academic community. keywords: Mentoring, improvement, quality, analysis, publication.